Analysis of Figurative Language in Owl City Lyricsâ€œVanilla Twilightâ€, â€œThe Saltwater Roomâ€ andâ€œLonely Lullabyâ€ - Rizki Puspita Sari; Masulah -; Ari Setyorini (Tell : Teaching of English Language and Literature Journal, 2014)
This article entitled Analysis of figurative language in Song â€œVanilla Twilightâ€, â€œThe Saltwater Roomâ€, and â€œLonely Lullabyâ€ by Owl City. Object analysis is Owl City songs. Problems in this research is finding a figure of speech and meaning that may be contained in the lyrics Owl City. This study aims to find the figure of speech in the Owl City song and what the meaning of the song. This study uses qualitative methods. The qualitative approach is one in which the Inquirer Often makes knowledge claims based primary social constructs a history. Data collection techniques used observational data. Data analysis techniques the phase when the researcher precedes the data after the data are collected.The figurative languageare found in the lyrics of songs like personification, similes, symbols, alliteration, hyperbole, repetition, and allegory, figures of speech and alliteration rarely. Then, total meaning are found in the lyric.